2016
DOI: 10.3390/cryst6110142
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Light Microscopy Study on the Reentrant Phase Transition in a (Ba1 – xKx)Fe2As2 Single Crystal with x = 0.24

Abstract: A sequence of structural/magnetic transitions on cooling is reported in the literature for hole-doped iron-based superconductor (Ba 1 − x K x )Fe 2 As 2 with x = 0.24. By using polarized light microscopy, we directly observe the formation of orthorhombic domains in (Ba 1 − x K x )Fe 2 As 2 (x = 0.24) single crystal below a temperature of simultaneous structural/magnetic transition T N~8 0 K. The structural domains vanish below~30 K, but reappear below T = 15 K. Our results are consistent with reentrance transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The similar feature had been observed in Ba(Fe 1−x Co x ) 2 As 2 , where the presence of fine orthorhombic structure domains leads to the J c maximum [10]. The orthorhombic structure domains have been directly observed in the parent compounds and underdoped samples by using polarized light microscopy [10,[51][52][53]. In the previous studies on (Ba 1-x K x )Fe 2 As 2 , high J c were observed between 0.25 0.30, and J c exceed 10 5 A/cm 2 at T=25K and H=6 T for x=0.30 [5][6].…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The similar feature had been observed in Ba(Fe 1−x Co x ) 2 As 2 , where the presence of fine orthorhombic structure domains leads to the J c maximum [10]. The orthorhombic structure domains have been directly observed in the parent compounds and underdoped samples by using polarized light microscopy [10,[51][52][53]. In the previous studies on (Ba 1-x K x )Fe 2 As 2 , high J c were observed between 0.25 0.30, and J c exceed 10 5 A/cm 2 at T=25K and H=6 T for x=0.30 [5][6].…”
Section: Resultssupporting
confidence: 52%
“…As far as pinning sources are concerned, the formation of structural domains in the orthorhombic phase has been well studied both in Ba(Fe 1−x Co x ) 2 As 2 and (Ba 1-x K x )Fe 2 As 2 by using polarized light microscopy [10,[51][52][53]. The domain walls extend throughout the samples and act as the extended pinning centers.…”
Section: E Pinning Mechanismsmentioning
confidence: 99%
“…The temperature-dependent resistivity of the sample used in this study follows previous reports 15,17 with small upturn in ρ(T ) below 60 K signalling tetragonal-to-orthorhonbic phase transition at T C2 and small down-turn feature at 37 K signalling re-entrance of the tetragonal phase at T C4 [18][19][20] . These features in the ρ(T ) lead to clear anomalies in the temperature-dependent resistivity derivative, dρ(T )/dT , see left panels of Fig.…”
Section: Stress-dependence Of Structural Transitionssupporting
confidence: 77%
“…This stress value naturally varies on cooling, see right panel. The inset shows ρ(T ) of the sample over the whole range up to 300 K, with the resistivity value fixed at ρ(300K) =300 µΩcm 20 . The right panel shows temperature dependence of x =0.25, zoomed in the range of tetragonal to orthorhombic phase transition (left panel).…”
Section: Electrical Resistivity Measurements In Mechanical Detwinning Devicementioning
confidence: 99%
“…(3) Superconductivity competes with the t-SDW phase more strongly than with the o-SDW phase [17,[29][30][31]. Upon cooling from the t-SDW phase into the superconducting phase, the lattice symmetry may even go back to C 2 [29,30,32].…”
mentioning
confidence: 99%